Green Credit Policy and the Sustainability of Green Innovation: Symbolic or Substantive Responses from High-Polluting Firms - Wang, Dicheng; Zhang, Qian; Jin, Ziyue; Li, Han (Asia Pacific Economic and Management Review, 2026)
Amid global carbon neutrality and sustainable development goals, and China’s transition toward high-quality green and sustainable growth, this study investigates how the Green Credit Policy (GCP) influences the sustainable innovation performance of high-polluting firms. Using Chinese A-share listed firms from 2007 to 2019 and a difference-in-differences (DID) design, we exploit the implementation of the GCP as a quasi-natural experiment to assess its long-term sustainability effects on corporate green transformation. The results reveal that while the GCP significantly promotes symbolic green innovation associated with regulatory compliance, it does not substantially enhance substantive green innovation, raising concerns about the effectiveness of green finance in fostering authentic and high-quality sustainability-oriented innovation. Further analysis shows pronounced heterogeneity across firm types. State-owned enterprises (SOEs) and large firms exhibit improvements in substantive green innovation, thereby contributing more effectively to long-term environmental sustainability and green transformation, whereas non-SOEs and small firms experience tightened financial constraints that crowd out R&D investment, ultimately undermining their sustainable innovation capacity. A series of robustness tests confirms the reliability of these findings. Overall, this study advances the literature on green finance and corporate sustainability by revealing firms’ strategic compliance behavior under sustainability-oriented financial regulation, highlighting uneven sustainability outcomes across firm types, and offering policy implications for refining green credit mechanisms to better support genuine green innovation and long-term sustainable development.